2006
DOI: 10.1002/mds.21277
|View full text |Cite
|
Sign up to set email alerts
|

Hypomyelinating leukoencephalopathy with paroxysmal tonic upgaze and absence of psychomotor development

Abstract: Hypomyelinating leukoencephalopathies are characterized by a substantial and permanent deficit in myelin deposition in the brain. Although our knowledge and understanding of the etiology of white matter diseases has progressively increased, many cases with this disorder remain undiagnosed, despite extensive evaluations. Recently, new disease entities have been defined by combining magnetic resonance imaging pattern recognition and clinical features. We describe a 1-year-old Ashkenazi Jewish girl with a hypomye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Paroxysmal tonic upgaze has also been described in children with cerebellar ataxia and developmental delay caused by mutations in GRID2, and in sporadic cases of Beckwith‐Wiedemann syndrome, genetically undefined hypomyelinating leukoencephalopathy, CACNA1A mutation with episodic ataxia, and childhood absence epilepsy . Again, at this time, it is not clear whether these represent OGC or some other ocular movement disorder.…”
Section: Ogc Mimickers/differential Diagnosismentioning
confidence: 99%
“…Paroxysmal tonic upgaze has also been described in children with cerebellar ataxia and developmental delay caused by mutations in GRID2, and in sporadic cases of Beckwith‐Wiedemann syndrome, genetically undefined hypomyelinating leukoencephalopathy, CACNA1A mutation with episodic ataxia, and childhood absence epilepsy . Again, at this time, it is not clear whether these represent OGC or some other ocular movement disorder.…”
Section: Ogc Mimickers/differential Diagnosismentioning
confidence: 99%
“…4,6 Recently, Blumkin et al reported a patient whose cranial magnetic resonance imaging demonstrated severe hypomyelination, thin corpus callosum, and progressive brain atrophy. 2 As a result, in consideration for the paroxysmal tonic upgaze cases with delayed myelination, hypomyelination, or demyelination, as in our case, disorder of myelin can be important in the pathogenesis of paroxysmal tonic upgaze. Neuroimaging must be performed in all cases with paroxysmal tonic upgaze.…”
Section: Discussionmentioning
confidence: 68%
“…1 In the further cases with paroxysmal tonic upgaze learning disabilities, abnormal neurologic findings such as ataxia, chromosomal abnormality, familial inheritance, and abnormal neuroimaging findings have also been reported. [2][3][4][5][6] We report a patient who had paroxysmal tonic upgaze and demyelinating lesions on his cranial magnetic resonance imaging.…”
mentioning
confidence: 99%
“…The reported results of imaging studies for most children with PTU have been normal, with the exception of some cases with hypomyelination or delayed myelination, or with lesions within the oculomotor pathway, 12,13 which is mostly located within the midbrain and brainstem.…”
Section: Discussionmentioning
confidence: 98%